Predictors of Stent Restenosis in Han and Uygur Patients with Coronary Heart Disease after PCI in the Xinjiang Region - Jiao Wang; Yuchun Yang; Lei Zhang; Pengyi He; Huyati Mu (Cardiology Research and Practice)
Background. Stent restenosis after PCI seriously affects the efficacy and prognosis; therefore, the study of ISR risk factors has become an urgent topic to be solved. Objective. To investigate the risk factors for in-stent restenosis (ISR) after percutaneous coronary intervention (PCI) in Han and Uygur patients with coronary heart disease. Methods. The clinical data of 345 Han and 127 Uygur patients who underwent intracoronary stent implantation were divided into an ISR group and a non-ISR group. The general clinical data, laboratory indicators, and coronary artery lesions were compared. Results. Age (OR = 1.040, 95% CI: 1.006∼1.075), triglycerides (OR = 1.440, 95% CI: 1.050∼1.973), total cholesterol (OR = 5.256, 95% CI: 2.826∼9.773), and ApoB (OR = 137.540, 95% CI: 11.364∼899.455) were independent risk factors for ISR after PCI in the Han patients, while ApoAI (OR = 0.002, 95% CI: 0.001∼0.011), MCV (OR = 0.824, 95% CI: 0.744∼0.911), MCH (OR = 0.421, 95% CI: 0.324∼0.548), and MCHC (OR = 0.934, 95% CI: 0.903∼0.965) were protective factors of ISR after PCI in Han patients, and the logistic regression equation composed of various factors predicted that the area under the ROC curve of ISR was 0.905. ApoB (OR = 11.571, 95% CI: 1.667∼80.340), Gensini score (OR = 1.017, 95% CI: 1.003∼1.031), and diabetes history (OR = 3.474, 95% CI: 1.189∼10.151) were independent risk factors for ISR after PCI in Uygur patients, and the area under ROC curve of ISR predicted by logistic regression equation is 0.807. The predictive efficiency of the Gensini score and ApoB level for ISR in Uygur patients was higher than that in Han, while the predictive efficiency of levels of ApoAI and MCH for ISR in Han patients was higher than that in Uygur (P<0.05). Conclusion. The independent risk factors for ISR after PCI in Han and Uygur patients in Xinjiang are different.